E-Marketing Strategies Imperative for Business Performance in Nigeria - Agada, Solomon Agada (NINM International Academy of Marketing, 2013)
The present study explored the invaluable impact of E-marketing and its significance on modern business performance - particularly in banking services in Nigeria. Nigerian banks are consciously making efforts to key into this concept with most banks transmitting information about customers' bank accounts through the internet using email, telephone, and other telecommunication network facilities. Extant literature were explored and discussed. Top management support was identified as crucial in the acquisition and diffusion of innovation such as E-marketing with empirical evidence that there is a positive effect of leadership support on innovation adoption. The hig her the appreciation of the benefits of e-commerce by management, the more likely they are to set aside organizational resources necessary to adopt and implement e-commerce. To carry along all stakeholders and for e-commerce to thrive, sellers and buyers have to be willing to exchange goods and services for money online. Technology will definitely transform not only the "front office" aspect of business enterprise, but will also manage the company's relationship with their customers, and success will be measured differently, then according to the return on customer relationship or customer desire.
Keywords: Marketing; Banking services; Business performance; Internet; Management; Nigeria